The direct cost incurred by patients and caregivers in diagnosing and managing prostate cancer in Ghana - Ebenezer Wiafe; Kofi Boamah Mensah; Kwaku Addai Arhin Appiah; Frasia Oosthuizen; Varsha Bangalee (BMC, 2022)
Abstract Background Over the years, the prevalence of prostate cancer (PCa) has been on the increase. Poor prognosis has been a reflection of increased advance-staged diagnosis and inadequate financial assistance. The prioritization of resources cannot be effective enough to factor in the unexpected economic burden resulting from ill health unless health economic approaches are utilized to estimate the cost of diseases including PCa. With the absence of data on the cost of PCa in Ghana, and the evidence of the benefits of PCa cost-of-illness studies on cancer financing, it has become imperative to investigate the direct health cost of PCa on patients and careers. Hence, we investigate the cost of PCa diagnosis and management, the availability and prices of PCa medications, and the affordability of PCa care in Ghana. Methods The prevalence approach to cost-of-illness studies was adopted in this study through a random selection of two (2) hospitals, four (4) private laboratories, and ten (10) private community pharmacies in the Ashanti Region of Ghana. The diagnostic and management cost of PCa was investigated through the application of validated data collection instruments to representatives of the selected hospitals and laboratories. The availability and prices of PCa medications were studied with the administration of a validated tool to representatives of the selected pharmacies. The data were analyzed with Microsoft Excel Spreadsheet and the affordability of care was assessed considering the 2021 Ghana National Daily Minimum Wage (GNDMW). Results The cost of diagnosing non-metastatic and metastatic PCa were respectively estimated at GHC 1686.00 ($ 290.58) and GHC 6876.00 ($ 1185.09). Radical prostatectomy, as a management option, was estimated at GHC 2150.00 ($ 370.56) higher than Extended Beam Radiotherapy (GHC 2150.00: $ 370.56). The mean PCa drug availability for the sampled pharmacies around the public hospital, all the sampled pharmacies, and around the private hospital were respectively 61.54, 51.54, and 41.54%. None of the sampled drugs at the stated strengths had a 100% availability. A 6-month androgen deprivation therapy employing goserelin was GHC 3000.00 ($ 517.05). The median drug price ratio (MDPR) was 0.72 - 15.38, with generic bicalutamide 150 mg tablets as the cheapest and generic flutamide 250 mg tablets as the most expensive. Conclusion The diagnostic and management cost of PCa currently overwhelms the average Ghanaian because the minimum daily wage in 2021 is GHC 12.53 ($ 0.46). A higher economic burden was associated with metastatic PCa and hence, the need for strategies to improve early detection. Also, the inclusion of PCa management in the National Health Insurance Scheme would lessen the financial burden of the disease on patients and careers, and improve management outcomes.